2013
DOI: 10.7554/elife.00790
|View full text |Cite
|
Sign up to set email alerts
|

Fungal effector Ecp6 outcompetes host immune receptor for chitin binding through intrachain LysM dimerization

Abstract: While host immune receptors detect pathogen-associated molecular patterns to activate immunity, pathogens attempt to deregulate host immunity through secreted effectors. Fungi employ LysM effectors to prevent recognition of cell wall-derived chitin by host immune receptors, although the mechanism to compete for chitin binding remained unclear. Structural analysis of the LysM effector Ecp6 of the fungal tomato pathogen Cladosporium fulvum reveals a novel mechanism for chitin binding, mediated by intrachain LysM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
250
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 220 publications
(259 citation statements)
references
References 45 publications
7
250
0
2
Order By: Relevance
“…A recent study revealed that intermolecular dimerization of Arabidopsis thaliana CERK1, the chitin elicitor receptor kinase with three LysM motifs, is crucial for binding chitin oligosaccharides and its signaling function . Ecp6, the ortholog of Slp1 in the fungal pathogen Cladosporium fulvum (de Jonge et al, 2010), also has three LysM motifs that form intrachain LysM dimers to provide a groove for chitin binding (Sánchez-Vallet et al, 2013). To further determine how N-glycosylation affects the chitin binding activity of Slp1, it will be important to compare differences in the crystal structure of Slp1 between N-glycosylated and nonglycosylated Slp1.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study revealed that intermolecular dimerization of Arabidopsis thaliana CERK1, the chitin elicitor receptor kinase with three LysM motifs, is crucial for binding chitin oligosaccharides and its signaling function . Ecp6, the ortholog of Slp1 in the fungal pathogen Cladosporium fulvum (de Jonge et al, 2010), also has three LysM motifs that form intrachain LysM dimers to provide a groove for chitin binding (Sánchez-Vallet et al, 2013). To further determine how N-glycosylation affects the chitin binding activity of Slp1, it will be important to compare differences in the crystal structure of Slp1 between N-glycosylated and nonglycosylated Slp1.…”
Section: Discussionmentioning
confidence: 99%
“…Avr4 is a chitin-binding protein that protects the fungus from plant chitinases, and it is recognised by the Hcr9-4D LRR-RLP gene located at the Cf-4 locus (Thomas et al 1997; Van Den Burg et al 2006). Ecp6, a LysM protein, also binds to chitin oligomers released by the action of host chitinases, which in turn minimises recognition by the host (Sánchez-Vallet et al 2013). Reduced effector expression was proposed to contribute to the reduced virulence of cfwor1 mutants (Okmen et al 2014).…”
Section: Fungal Potential Against Host Immune Systemmentioning
confidence: 99%
“…Thus, adapted pathogens must overcome PTI in order to grow and to cause disease. A common mechanism for PTI suppression is the secretion of pathogen proteins, called effectors, into the apoplast or inside host cells (Dou and Zhou, 2012;Sánchez-Vallet et al, 2013). Plants also can recognize specific intracellular pathogen effectors using resistance proteins and induce effectortriggered immunity (ETI; Chiang and Coaker, 2015).…”
mentioning
confidence: 99%